Influence of soil salinity on the bearing capacity of the frozen wall (Fracture and Structural Integrity, 2024)
The article describes the results of laboratory studies on the unfrozen water content and ultimate long-term strength of frozen clay and chalk samples in the temperature range from −10 to −25 °C. The soil samples contained dissolved salt in the pore space, with three types of salts (NaCl, KCl, and CaCl2) being considered. The findings indicate that the influence of the content and type of dissolved salt on the ultimate long-term strength of soils is realized indirectly through the unfrozen water content. In this case, the soil freezing characteristic curve in the region of negative temperatures significantly depends on both the type of dissolved salt and its quantity. The experimental data obtained were used to parameterize the model and calculate the maximum bearing capacity of the frozen wall (FW) in the presence of dissolved salts in the volume of frozen soils. It has been demonstrated that the decrease in the maximum FW bearing capacity is substantial with the appearance of dissolved salt in the pore space of the soils. This decrease is at-tributed to the combined effects of two factors: 1) a reduction in the FW thickness and 2) a decrease in the frozen soil strength due to an increase in the amount of unfrozen water content in the soil pore space. The second factor is deemed more significant.
Keywords: Artificial ground freezing; Frozen wall; Dissolved salt; Ultimate long-term strength; Unfrozen water content; Mine shaft